2016
DOI: 10.1177/1049909116672641
|View full text |Cite
|
Sign up to set email alerts
|

Health-Care Workers’ Judgments About Pain in Older Palliative Care Patients With and Without Delirium

Abstract: Delirium complicates pain assessment and management in advanced cancer. This retrospective cohort study compared health-care workers' (HCWs) cancer pain judgments between older patients with advanced cancer with and without a diagnosis of delirium. We reviewed HCWs' daily chart notations about pain presence and good pain control in 149 inpatients with advanced cancer, ≥65 years of age, admitted to a palliative care inpatient unit. Any day with 1 or more notations of pain presence was counted as 1 day with pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Given that delirium is perceived as a very distressing condition by those who have experienced it and recovered (Kuusisto-Gussmann et al, 2021), it is possible that the dying patient with an altered level of consciousness is equally distressed. The findings of this integrative review agree with the previously reported findings regarding the lack of available guidance, and the difficulty in assessing the care needs of the voiceless and vulnerable dying patient with delirium (Gao et al, 2013; Lawlor et al, 2014; Blinderman and Billings, 2015; Mah et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Given that delirium is perceived as a very distressing condition by those who have experienced it and recovered (Kuusisto-Gussmann et al, 2021), it is possible that the dying patient with an altered level of consciousness is equally distressed. The findings of this integrative review agree with the previously reported findings regarding the lack of available guidance, and the difficulty in assessing the care needs of the voiceless and vulnerable dying patient with delirium (Gao et al, 2013; Lawlor et al, 2014; Blinderman and Billings, 2015; Mah et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, only one patient in the persistent‐delirium group was treated with pregabalin. The relationship between pain and delirium has been pointed out in areas such as palliative treatment and ICU, with an emphasis on assessment and management in these areas 29,30 . In addition, there is a report about elderly patients with dementia who have a fractured hip joint, in which a comparison is made between those elderly whose pain is controlled appropriately and whose pain is not well controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between pain and delirium has been pointed out in areas such as palliative treatment and ICU, with an emphasis on assessment and management in these areas. 29,30 In addition, there is a report about elderly patients with dementia who have a fractured hip joint, in which a comparison is made between those elderly whose pain is controlled appropriately and whose pain is not well controlled. The report shows that the latter group had a nine times higher occurrence of complications from delirium, implying that pain is a cause of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients with HD experienced higher levels of distress associated with pain compared with their counterparts without HD. Previous research showed that pain was substantially less well managed for patients with palliative care cancer with HD than for those without HD (Mah et al., 2017). Health professionals also observed that patients with HD tended to experience more intense and intractable pain (Mah et al., 2017).…”
Section: Discussionmentioning
confidence: 99%